3D CNTs Networks Enable MnO2 Cathodes with High Capacity and Superior Rate Capability for Flexible Rechargeable Zn–MnO2 Batteries. Issue 12 (3rd September 2019) - Zhang, Xiyue; Wu, Shuwei; Deng, Shengjue; Wu, Weixing; Zeng, Yinxiang; Xia, Xinhui; Pan, Guoxiang; Tong, Yexiang; Lu, Xihong
Abstract: The advancement of flexible rechargeable Zn–MnO2 batteries largely relies on directional design and fabrication of flexible cathode materials. However, the sluggish electron transfer and inferior mass diffusion rate of MnO2 cathodes hinder their application in high‐power systems. Herein, the design of flexible 3D carbon nanotube (CNT) conductive networks as excellent electron and charge transfer substrates is reported to achieve a high‐rate MnO2 cathode. With further structural protection of conductive poly(3, 4‐ethylenedioxythiophene) (PEDOT), Zn 2+ storage kinetics in the composite CNT/MnO2 /PEDOT (denoted as CMOP) the cathode is optimized to deliver high capacity of 306.1 mAh g −1 at 1.1 A g −1 and superior rate capability of 176.8 mAh g −1 when the current density increases by tenfold (10.8 A g −1 ), representing a state‐of‐the‐art of current MnO2 based cathodes. Moreover, the as‐assembled quasi‐solid‐state Zn–CMOP batteries with good mechanical properties can afford a high energy density of 379.4 Wh kg −1 (17.5 mWh cm −3 ) and a peak power density of 17.1 kW kg −1 (0.8 W cm −3 ). This innovative achievement will be a critical step forward toward next‐generation quick charging electronics. Abstract : 3D carbon nanotube (CNT) conductive networks are demonstrated as excellent electron and charge transfer substrates to improve the Zn 2+ storage kinetics of a CNT/MnO2 /poly(3, 4‐ethylenedioxythiophene)(PEDOT) (CMOP) cathode, resulting in a superior rate performance of 306.1 mAh g −1 at 1.1 A g −1 and 176.8 mAh g −1 at 10.8 A g −1 with a good durability after 2000 cycles.